2001
DOI: 10.1097/00003246-200102000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Bronchoscopy with bronchoalveolar lavage via the laryngeal mask airway in high-risk hypoxemic immunosuppressed patients

Abstract: Application of the LMA appears to be a safe and effective alternative to intubation for accomplishing FOB with BAL in immunosuppressed patients with suspected pneumonia and severe hypoxemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 39 publications
0
23
0
2
Order By: Relevance
“…Given the large number of causes of ARF in haematological patients and the frequent combination of multiple causes in individual patients, greater clinical experience might lead to better patient management [10]. In particular, identification of the cause of ARF is associated with improved survival [11,14,28] and might benefit from greater clinical experience. Although the use of noninvasive mechanical ventilation and close collaboration with haematological consultants may help to manage these patients [28,29], neither variable was independently associated with mortality in the present study, suggesting that intensive care specialists may acquire the skills needed to achieve optimal management provided they see a sufficient number of patients with haematological malignancies and ARF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the large number of causes of ARF in haematological patients and the frequent combination of multiple causes in individual patients, greater clinical experience might lead to better patient management [10]. In particular, identification of the cause of ARF is associated with improved survival [11,14,28] and might benefit from greater clinical experience. Although the use of noninvasive mechanical ventilation and close collaboration with haematological consultants may help to manage these patients [28,29], neither variable was independently associated with mortality in the present study, suggesting that intensive care specialists may acquire the skills needed to achieve optimal management provided they see a sufficient number of patients with haematological malignancies and ARF.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, identification of the cause of ARF is associated with improved survival [11,14,28] and might benefit from greater clinical experience. Although the use of noninvasive mechanical ventilation and close collaboration with haematological consultants may help to manage these patients [28,29], neither variable was independently associated with mortality in the present study, suggesting that intensive care specialists may acquire the skills needed to achieve optimal management provided they see a sufficient number of patients with haematological malignancies and ARF. In haematological patients with ARF, the number of ICU admissions is rising and life-sustaining treatments (most notably mechanical ventilation) are increasingly used [6,8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient agitation may lead to desaturation and possibly compromise the success of the FOB-BAL procedure (25). One previous study described the difficulties in performing bronchoscopy without sedation, with analgosedation used in all patients (14). LMAs provide upper airway patency even in cases of deep sedation or general anaesthesia, which subsequently ensures excellent visualization of the vocal cords, glottis and trachea without decreasing the airway diameter as do tracheal tubes, thus avoiding increases in airway resistance (9,10,(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…An advantage of LMA is that it can be blindly inserted without laryngoscopy; thus, cardiovascular responses to the introduction of an LMA are less severe than those induced by tracheal intubation (11,12). The LMA technique for both spontaneous and controlled ventilation is reportedly both safe and effective (13), and a recent study demonstrated that FOB-BAL can be safely and effectively performed with an LMA in immunosuppressed patients with pneumonia and severe hypoxaemia (14).…”
Section: Introductionmentioning
confidence: 99%